Stimulator of interferon genes promotes diabetic sarcopenia by targeting peroxisome proliferator activated receptors γ degradation and inhibiting fatty acid oxidation - Sen‐bo Yan; Huan Liang; Peng Zhan; Hui Zheng; Qin‐xiao Zhao; Zi‐jie Zheng; Hui‐xia Lu; Guo‐kai Shang; Xiao‐ping Ji (Wiley, 2023)
Abstract Background Declined skeletal muscle mass and function are inevitable consequences of long‐term diabetes and bring about many adverse events. Muscle fibre atrophy and interstitial fibrosis are major pathological manifestations of diabetic sarcopenia. Stimulator of interferon genes (STING) participates in various metabolic diseases. We aimed to explore whether and how STING regulates the above pathological manifestations of diabetic sarcopenia. Methods Wild‐type and STINGgt/gt C57BL/6J mice and C2C12 myotubes were used to study the role of STING in the regulation of diabetic sarcopenia and the underlying mechanisms. Results STING was abnormally activated in diabetic muscles and in PA‐treated myotubes (P < 0.01 for all parameters). The diabetic mice demonstrated decreased forelimb grip strength, lean mass, muscle weight and hanging impulse, which were improved by STING deficiency due to alleviated muscle fibre atrophy and interstitial fibrosis (P < 0.05 for all parameters). STING deficiency alleviated muscle fibre atrophy through the following mechanisms. Firstly, STING deficiency or inhibition increased the contents of pDRP1Ser616, PINK1, Parkin and LC3‐II, decreased p62 content, and increased the amount of mito‐Keima fluorescent dots at 578 nm in diabetic state (P < 0.05 for all parameters), suggesting improved mitofission and mitophagy. Secondly, STING deficiency or inhibition increased the expression of pAKTSer473 and GLUT4 post‐insulin change in diabetic state (P < 0.05 for all), indicating alleviated insulin resistance (IR). Mechanically, STING deficiency or inhibition increased peroxisome proliferator activated receptors γ (PPARγ) protein content by reducing the degradation of ubiquitinated PPARγ through the proteasome pathway and thus increased the expression of fatty acid oxidation (FAO)‐related proteins in diabetic state (P < 0.05 for all parameters). Decreased expression of FAO‐related proteins caused by PPARγ inhibition abolished the improvements in mitofission, mitophagy and IR achieved by STING inhibition in PA‐treated myotubes and thus promoted muscle fibre atrophy (P < 0.05 for all parameters). STING deficiency alleviated interstitial fibrosis by decreasing TGFβ1 expression in diabetic state and TGFβ1 promoted the fibrogenic differentiation of fibro‐adipogenic progenitors (P < 0.05 for all parameters). PPARγ inhibition abolished the effect of STING inhibition on reducing TGFβ1 content in PA‐treated myotubes (P < 0.01). Conclusions STING deficiency exerted protective effects in diabetic sarcopenia by inhibiting the degradation of ubiquitinated PPARγ through the proteasome pathway and enhancing PPARγ‐mediated FAO, which alleviated muscle fibre atrophy by promoting mitophagy and ameliorating IR, and alleviated interstitial fibrosis by reducing TGFβ1 production and suppressing the fibrogenic differentiation of fibro‐adipogenic progenitors.